Attitude to food supplement use: a survey promoted by the Italian Society of Pediatric Allergy and Immunology - Giorgio Ciprandi; Maria Daglia; Giulia Brindisi; Francesco Paolo Brunese; Giulio Dinardo; Alessandra Gori; Cristiana Indolfi; Matteo Naso; Enrico Tondina; Chiara Trincianti; Attilio Varricchio; Anna Maria Zicari; et al. (BMC, 2024)
Abstract Food supplements are defined as foodstuffs the purpose of which is to supplement the normal diet and which are concentrated sources of nutrients or other substances with a nutritional or physiological effect, often referred to as nutraceuticals, may exert benefit to the human body. Their use is increasing worldwide, including Europe and in Italy. However, some doctors are skeptical about their effectiveness and safety. This reluctance may depend on poor knowledge of the mechanisms of action and clinical evidence in literature. The Italian Society of Pediatric Allergy and Immunology (SIAIP) promoted the institution of an ad hoc Committee. The first initiative performed by this Committee was the administration of a questionnaire to the members of SIAIP. The results of this survey provided interesting results. Most pediatricians know the food supplement concept but frequently need help understanding the mechanisms of action. Most prescribe food supplements, mainly for preventing infections or enhancing immune defense. In addition, they prefer to use food supplements as cycles or add-on therapy. Finally, most participants like to attend events on this issue and contribute to new evidence through trials. In conclusion, this survey underscores the relevance of food supplement issues and attests to interest in this topic. However, there is a need to provide information and promote studies on this matter.